ALIH KODE DALAM BAHASA SMS - Ana Rosmiati (Pendhapa, 2011)
The aims of this research are to find out  the forms of change of codes in the forms and functions in SMS (Short Message Service) discourse.            The population of this research was all of the utterances discovered in SMS language discourse from 2004 up to 2008. The utterances in SMS discovered in some cellular phones Sony Ericcsson K700i, Nokia 3100, Nokia 6030, Nokia 7610, Nokia N 81, Samsung N 620, Samsung E110, Motorola C15, and Sony Ericsson K310i in Surakarta area were used as a sample of this research. The data was collected by observation method of listening and interview with some informants endorsed with a noting technique. The writer directly sent SMS to some participants to validate the data. The data is analyzed by using padan pragmatic method to identify the form and structure of the discourse and the factors influencing SMS language. Identity method  is used to identify and classify lexical and grammatical aspects found in this discourse endorsed with delection and substitution techniques.            The result of this research showed that SMS language was a written discourse in the form of a dialogue between a speaker and interlocutor making use of the facilities in cellular phones. The internal change of code covered : the change of code of Indonesia standard variant into Indonesia non-standard variant , the change of code of Indonesia non-standard variant into Indonesia standard variant. The external change of code covered :  the change of code of Indonesia language into Kromo (high level of Javanese language), the change of code of Indonesia language into Madya (mid level of Javanese language), the change of code of Ngoko (low level of Javanese language) into Indonesia language,  the change of code of Javanese language into English,  the change of code of Kromo (high level of Javanese language) into English,  the change of code of Ngoko (low level of Javanese language) into English,  the change of code of Indonesia language into English, the change of code of non-standard Indonesia language into English, the change of code of Indonesia language into English.